ELEMENTS OF BUILDING CONTENT FOR GOVERNMENT WEBSITES: : (An Experimental Study) - Farouk Radwan, Ahmed; Omar Mohamed, Ahmed (ALBAHITH ALALAMI, 2019)
The study dealt with measuring the impact of the availability of each of the content elements of the interaction, electronic services, and information on the evaluation of the users of the government website for its effectiveness in terms of the site’s functions and for measuring the site’s ability to present the organization’s tasks to customer groups.Authority is concerned with measuring the confidence of customers in the content of the site, and in the organization as a whole. Validity is related to measuring the effectiveness of employing the site’s content to achieve the goal of its creation and in communicating with customers. Availability It is for measuring the ease of use of the site. The relevance, which means measuring the compatibility of the site’s form and content with the nature and identity of the governmental organization. Then, presentation tools which are for measuring the multiplicity of content presentation tools.And that is through an experimental study that relied on building a virtual government website, which was designed in terms of form and content in four copies. The content elements for each version were controlled. Then, each site was made available through an experimental group that used it and navigating its parts. Later, testing of a five-element scale was choosing to measure each group’s perception of site quality.The study reached a number of results, the most important of which is the absence of sufficient information about the organization on its website; and the absence of information on the tasks and services performed by the government website that leads to a poor evaluation of the site's users in terms of the site's ability to introduce the organization and achieve its functions and support interaction with clients; the confidence in the site in terms of information and services it provides; and in terms of providing privacy and maintaining customer data; its ease of use and identification of its components and content and the employment of its tools.Its ability to express the government’s identity and representation to the organization after it is one of its communicative methods. As well as the ability of site users to deal with multiple content tools with their different capabilities and categories. The absence of interaction tools on the government’s website, moreover, leads to a poor evaluation of the site’s users in terms of the website’s ability to achieve e-participation standards and continuous communication with customers.; as well as the ease of use.The absence of government service delivery through the organization's website, however, leads to a poor assessment of site users for quality elements.